Menelisik Platform Digital Dalam Teknologi Bahasa Pemrograman - Dea Nur zuraidah; Muhammad Fajar Apriyadi; Ahmad Rizal Fatoni; Muhammad Al Fatih; Yusuf Amrozi (Sekolah Tinggi Ilmu Komputer Binaniaga, 2021)
This study aims to identify the role of programing languages in building or developing a digital platform in accordance with the specifications of the needs desired by the community or users of the digital platform. The methodology of qualitative data description and literature study by Seeking information from various literatures and reference source related to the topics discussed. The data obtained is then analyzed and then concluded â€œso that result are obtainedâ€ from the topic. From this research, it can be concluded that programming languages play an important role in the development of a digital platform from browser, social media, to digital platform used for education.